Ciri Berpikir Ilmiah : Radikal, Sistematis, Rasional: Berpikir, Ilmu, Struktur - Luthfi Ilham Martua Tobing (Jurnal Penelitian Multidisiplin, 2022)
Thinking has indeed become a characteristic of humans. From the thinking model used will determine the character already acquired knowledge. Suppose only, a person who thinks with a radical, systematic, and rational thinking model, then will lead to a scientific character of knowledge. But arbitrary thinking models, will lead to non-scientific and messy knowledge. The author does not want to discuss arbitrary thinking models, but the author wants to discuss scientific thinking models, namely radical, systematic and rational. Looking at the importance and usefulness of scientific knowledge for intellectual civilization, the author was moved to launch this discussion. I built this study with the structure of the discussion contained in the formulation of the problem, namely, what is meant by scientific thinking? How to think radically, systematically and rationally in order to obtain scientific discovery? The end of the answer to the problem, aims to open the gates of scientific thinking to us. As a way of operating this research, the author uses a qualitative method with a "library research" approach. In this study, at least the conclusion that must be confirmed is, that to be categorized as scientific thinking is to think radically, systematically and rationally.